2016
DOI: 10.21037/jgo.2016.06.04
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between 5-fluorouracil/mitomycin and capecitabine/mitomycin in combination with radiation for anal cancer

Abstract: Background: There are no randomized phase III trials comparing 5-fluorouracil/mitomycin (FM) versus capecitabine/mitomycin (CM) in combination with radiotherapy (RT) for locally advanced anal cancer. We aim to evaluate the outcomes of patients treated with FM and CM at our institution. Conclusions: In our population-based study, CM and FM concomitant with RT achieved similar DFS and ACSS. Substitution of capecitabine for infusional 5-FU may therefore be a reasonable option for patients and physicians who prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Analysing the other protocols employed, 5% received the Mayo protocol, with the difference ( 5 OS: 55% versus 71%, p = 0.06) in favour of Nigro, and 4% received an alternative protocol, Capecitabine/MMC, with results showing slight benefit to the alternative protocol ( 5 OS: 91% versus 75%, p = 0.58), with no statistically significant difference in concordance with different authors based on non-inferior results, such as alternative therapies in patients who were not candidates for Nigro [23,29,43,44] for medical reasons, co-morbidities or lack of availability of infusion pumps to administer the Nigro protocol.…”
Section: Discussionmentioning
confidence: 79%
“…Analysing the other protocols employed, 5% received the Mayo protocol, with the difference ( 5 OS: 55% versus 71%, p = 0.06) in favour of Nigro, and 4% received an alternative protocol, Capecitabine/MMC, with results showing slight benefit to the alternative protocol ( 5 OS: 91% versus 75%, p = 0.58), with no statistically significant difference in concordance with different authors based on non-inferior results, such as alternative therapies in patients who were not candidates for Nigro [23,29,43,44] for medical reasons, co-morbidities or lack of availability of infusion pumps to administer the Nigro protocol.…”
Section: Discussionmentioning
confidence: 79%
“…from 2 studies [51,52]]. With respect to further outcomes reported in this summary, no significant differences were seen: CSS [Peixoto et al [53] did not find a significant difference; data not meta-analysed due to reporting issues], DFS [HR 1.13 (0.65-1.95), GRADE: ⨁◯◯◯, 300 pts. from 1 study [53]], CFS [HR 0.66 (0.28-1.54), GRADE: ⨁◯◯◯, 300 pts.…”
Section: Number Of Hits and Included Studiesmentioning
confidence: 80%
“…We identified four comparative cohort studies [50][51][52][53] in which a chemoradiation regimen with MMC and 5-FU was compared to chemoradiation with capecitabine (CCB) and 5-FU in patients with stage I-III anal cancer. These studies included one prospective cohort study [51] (serious risk of bias), and three retrospective cohort studies (two of these [50,52] rated as being at moderate and one [53] rated as being at serious risk of bias). Both interventions were roughly equivalent (i.e., had a narrow confidence interval around the line of no effect) with respect to OS [RR 0.98 (0.89-1.08) after a median follow-up of 2 years, GRADE: ⨁◯◯◯, 100 pts.…”
Section: Number Of Hits and Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 46 MMC has been suggested to convert unresectable patients to surgical candidates, 42 enhance the therapeutic effects of adjuvant CRT, 47 and improve local control 48 in periampullary adenocarcinoma. Although it has not been extensively studied in PDAC, MMC has been used in other cancers such as anal cancer, 49 , 50 , 51 and recent studies suggest its promising role in PDAC patients with a family history of PDAC and/or carcinomas with an inactivating mutation in a Fanconi anemia pathway gene (such as BRCA1, BRCA2 , or PALB2 ). 18 , 19 , 20 , 21 , 22 , 23 Study results from trial A demonstrated that having a family history of PDAC specifically resulted in a borderline significant improvement in OS (164.4 vs 28.7 months, P = .058).…”
Section: Discussionmentioning
confidence: 99%